Career Construction among Islamic Primary School Student: An Exploratory Study of Early Career Planning - Arifah Wulandari; Santy Andrianie; Elwas Berdha Krismona; Khairul Bariyyah; Badiyah Mirna Meilawati; Celso P. Resueṅo Jr.; Ivan Hasan Murad (Universitas Muhammadiyah Mataram, 2026)
Research on career development has largely focused on adolescents and young adults, leaving early career construction in primary education relatively underexplored, particularly in religious-based schooling context. Drawing on Career Construction Theory (CCT), this study examines how teachers in Islamic elementary schools facilitate students’ early career meaning making. A qualitative design was employed involving five Islamic elementary school teachers in Central and East Java, Indonesia, selected based on their teaching experience and involvement in student development programs. Data were collected through in-depth interviews and document observations and analyzed using reflexive thematic analysis framework. Credibility was ensured through data triangulation and member checking. The findings reveal that teachers act as key agents in fostering students’ early career awareness by integrating Islamic values such as responsibility, discipline, honesty, and respect into learning actions and school programs. Experiential activities, including career visits, school orientation programs, and interest-based extracurricular activities, support students’ early exploration and emerging career adaptability. This study contributes to the development of CCT by demonstrating how early career narratives can emerge within culturally and spiritually grounded educational environments. Pratically, the findings highlight the need for developmentally appropriate and culturally responsive career guidance frameworks in primary education. Future studies should incorporate students’ and parents’ perspectives to further capture the dynamics of early career constructions.